Life with the Esquimaux; a narrative of Arctic experience in search of survivors of Sir John Franklin's expedition. - Hall, Charles Francis, 1821-1871. (London, S. Low, Son, and Marston, 1865)
Arctic researches, and life among the Esquimaux. Mode of access: Internet.